2016
DOI: 10.1002/ajhb.22844
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the pectoral girdle in a sample of juveniles from the kellis 2 cemetery, Dakhleh Oasis, Egypt

Abstract: Changes in scapular body shape during ontogeny may be a reflection of the greater alterations taking place in the integrated morphology of the pectoral girdle during the biomechanical shift from crawling to bipedalism. Am. J. Hum. Biol. 28:636-645, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…The previous studies demonstrated a growth spurt starting at age 10 in females and age 14 in males, which cannot be confirmed in the current study due a truncation of the sample at age 13. The finding that scapular height grows faster than breadth is consistent with previous studies (Bleuze et al, ; Rissech & Black, ) and confirms the notion that with increasing age, the scapular body proportionately increases more in height than it does in width.…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies demonstrated a growth spurt starting at age 10 in females and age 14 in males, which cannot be confirmed in the current study due a truncation of the sample at age 13. The finding that scapular height grows faster than breadth is consistent with previous studies (Bleuze et al, ; Rissech & Black, ) and confirms the notion that with increasing age, the scapular body proportionately increases more in height than it does in width.…”
Section: Discussionsupporting
confidence: 91%